(untitled) (مجلة البحوث الأكاديمية, 2021)
In this study the total phenolics content expressed as gallic acid equivalents (GAE) was higher in raw mallow leaves (459 mg GAE/100g DW) than in raw Jew’s mallow leaves (339 mg GAE/100g DW). Results showed that, the concentration of total flavonoids in Jew’s mallow was: 189, 163, 156 in raw, cooked and aqueous extract respectively. Whereas were in mallow as following: 188 in raw mallow, 174 in cooked mallow and 165 in aqueous extract. The antioxidant activity of raw and cooked Jew’s mallow and mallow leaves and their aqueous phenolic extracts were: 2.947±0.09, 3.315±0.05, 9.4±0.04, 2.076±0.09, 2.440±0.02, 5.9±0.03, respectively. Phenolic compounds in raw and cooked Jew’s mallow and mallow leaves (mg/ 100g on dry weight basis) were: 2.2376 in raw Jew’s mallow, 1.9918 in cooked Jew’s mallow, 9.563 in raw mallow, 6.9432 in cooked mallow.